Consequences of Differentiated Leadership in Groups - Wu, Joshua B.; Tsui, Anne S.; Kinicki, Angelo J. (Academy of Management Journal, 2010)
This study addressed the unresolved issue of how differentiated leadership (leaders treating individuals within a group differently) affects group effectiveness. We developed and tested a group-level model involving group-focused and individual-focused leadership using three-phased survey data from 70 work groups in eight companies. Results showed that differentiated leadership within groups diminished group effectiveness through creating divergence in leader identification and member self-efficacy and lower group collective efficacy. At the same time, group-focused leadership facilitated group identification and collective efficacy, which positively contributed to group effectiveness. We discuss theoretical and managerial implications of the potential cost of differentiated leadership behaviors in groups.